Farm Parent and Youth Aspirations on the Generational Succession of Farming: Evidence From South India - Nandi, Ravi; Pratheepa, C. M.; Nedumaran, Swamikannu; Rao, Nitya; Rengalakshmi, Raj (Frontiers in Sustainable Food Systems, 2022)
Agriculture remains important in ensuring the food security of developing economies like India, yet increasing rural-urban migration, an ageing farm population, and waning interest of rural youth in agriculture are emerging concerns. This paper focuses on the aspirations of farm parents and their children in agriculture, the challenges they confront, and potential solutions. We draw on qualitative data from two rural sites in Southern India, different from each other in their agro-ecological and social contexts, to point to the material, social, relational, and structural factors shaping aspirations. Agrarian distress, resulting from both climate variability and market uncertainty, affects farm households’ socioeconomic status, resulting in farmers’ aspiration failure in relation to agriculture. Farm parents then focus on educating their children, aspiring for secure non-farm jobs for their sons and finding suitable marriage partners, also in non-farm employment, for their daughters. While this steer from parents discourages youth from aspiring to careers in agriculture, in reality, there is a wide gap in the achievement of aspirations and a majority of youth, especially young women, do end up working on their family farms. For the future development of agriculture and sustainable food systems, it is therefore important to protect young farmers from aspiration failures and enable them to innovate through appropriate policies.